Patient attitudes to clinical trials: development of a questionnaire and results from asthma and cancer patients. - Jenkinson, C; Burton, J; Cartwright, J; Magee, H; Hall, I; Alcock, C; Burge, S (2005)
OBJECTIVE: To develop a questionnaire to assess patients' views of clinical trials, and to report the results from the questionnaire in two patient groups: asthma and cancer. DESIGN: A 43 item questionnaire asking patients about their views to clinical trials was developed on the basis of interviews with trialists and focus groups with patients. The questionnaire was mailed to patients with a diagnosis of either asthma or cancer. A set of items was then selected, via statistical analyses, to form the core of the questionnaire. PARTICIPANTS: Patients with a diagnosis of cancer in one NHS Hospital Trust, and patients with a diagnosis of asthma in two NHS Hospital Trusts. RESULTS: Completed questionnaires were received from 353 cancer patients and 578 asthma patients. Factor analyses of the data indicated that 22 items contributed to five dimensions: 'positive beliefs', 'safety', 'information needs', 'negative expectations' and 'patient involvement'. Differences between asthma and cancer patients on these dimensions were small. A regression of these dimension scores against a variable asking if patients would be willing to take part in trials found that 'safety' and 'information needs' did not contribute significantly to the model for either asthma or cancer patients. CONCLUSIONS: A questionnaire has been developed for use in assessing patients' views towards clinical trials. Results from the surveys reported here suggest that patient views about the importance of trials and beliefs about the value of patient involvement are likely to be predictive of whether or not patients will agree to take part in a study.